Selfie-Taking and Marine Wildlife - More Harm Than Good? - Lueck, Michael (Wakayama University, 2023)
Since the introduction of the smartphone more than a decade ago, the way we take photos has changed. The rise of taking selfies - photos of oneself with the purpose to post them on social media - has brought with it concerns about significant risks, including the harm and even death of the photographers and/ or wildlife. Exemplified by marine wildlife photos, risks to both the photographers and the wildlife species photographed are being discussed. Positive outcomes for marine conservation are also introduced. Lastly, some possible management approaches will be provided.
Keywords: selfie; marine wildlife; conservation; risk taking